IMPLEMENTATION OF RECRUITMENT FOOD AND BEVERAGE SERVICE AT ARYADUTA HOTEL PEKANBARU - Noviandri Efrizal; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In facing new century and competition inter-hotel basically absolute need that of Human Resources is a vital important factor. It cannot be denied that companies and organizations will have a complex competition form with variation, identity and scope that may not be experienced previously yet.Factors of human resources are very complex wich means that this discussion includes the recruitment, selection, labors analysis, etc. From those series of activities it will be no doubt that labors recruitment process is a vital important matter at Aryaduta Hotel Pekanbaru which is one of hotel in Pekanbaru, Riau that are very rapidly developed in improving its efforts.The objectives of this research are: 1) To know the process of labors recruitment in modern economy, 2) to know the process of recruitment applied at Aryaduta Hotel Pekanbaru. The method used in this research is descriptive qualitative that is as a research process which produces qualitative data in the form of written or oral words from the people or subjects being observed.